Analyzing current digital healthcare trends using social networks - Baral, Sukanta Kumar 1966-; Goel, Richa 1980- (Advances in medical technologies and clinical practice (AMTCP) book series, 2024)
It is vital to define future policy orientations by understanding the link between stakeholders and industry-related concerns in order for digital health care solutions to be employed in practice. In order to analyze the network of the digital health care business, this book uses research articles, case studies, etc. that serve as the foundation for social discussions about such critical issues.